Réponses

2013-04-03T18:03:34+02:00

EXERCICE 40 :

 

3x + 2 = 2x - 5

3x + 2 - 2 = 2x -5 - 2

3x - 2x = 2x - 7 - 2x

x = - 7

 

-3x + 7 = 3x - 11

-3x + 7 - 7 = 3x - 11 - 7

- 3x - 3x = 3x - 18 - 3x

-6x / -6 = - 18 / -6

x = - 3

 

EXERCICE 42 :

 

2(x - 5) = 3x + 5

2x - 10 + 10 = 3x + 5 + 10

2x - 3x = 3x + 15 - 3x 

-x = 15

x = -15

 

-4(3 + x) = 2x - 6

- 12 - 4x + 12 = 2x - 6 + 12

- 4x - 2x = 2x + 6 - 2x

-6x / -6 = 6/ -6

x = - 1

2013-04-03T18:12:17+02:00

N°40:

a)  3x + 2 = 2x -5

     3x - 2x = -5+2

     1x = -3

     x = -3 sur 1 = -3

 

b)   -3x + 7 = 3x - 11

      -3x - 3x = -11 - 7

     -6x = -18

   x = -18 sur -6 = 3

 

N° 41:

a) -5x + 4= 6x + 8

    -5x -6x = 8-4

   -11x = 4

   x= 4 sur 11 = 0.36

 

b) 5-9x = -3x +2

    5 -2 = -3x + 9x

    3=6x

   x= 6 sur 3 = 2

 

Je réfléchis pour le 42.

 

Je suis sure pour tous ce que je t'ai écris.

 

J'espère t'avoir aider :)